REFORMASI BIROKRASI BIDANG ORGANISASI DI KABUPATEN PEKALONGAN - Lituhayu, Dyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
This study will take a focus on target area son the establishment of organization apparatus that is able torespon and expand the ability of the public. Issues examined include how the condition of the field of organizationapparatus in Pekalongan and how efforts to improve the performance of field organization in Pekalongan. Theresults showed that the Pekalongan government efforts, among others, by realizing an effective and efficientgovernment, in achieving good governance by improving the responsiveness of the public organization. Toimprove performance organization apparatus needs to be donesuch asa maximize professional values withimplementing laws that exist to achieve organization performance by providing clear targets regarding theminimum that should be done by the employee each day, as an effort to the task at hand.